Mental distress is associated with injury and illness in elite Para athletes: a 44-week prospective study over 13 860 athlete days - Bentzen, M.; Kenttä, G.; Derman, W.; Wik, E. H.; Havela, J.; Karls, T.; Stenman, A.; Fagher, K. (BMJ Open Sport & Exercise Medicine, 2025)
Background The interest in elite athletes` mental health has increased over the past decade. However, there is still a paucity in the literature concerning elite Para athletes` mental health and its association with injuries and illnesses affecting athletes` participation in sports.